2006
DOI: 10.3917/ls.118.0043
|View full text |Cite
|
Sign up to set email alerts
|

Idéologies et pratiques du multilinguisme au québec : luttes et mutations dans un site de la nouvelle économie

Abstract: Distribution électronique Cairn.info pour Éditions de la Maison des sciences de l'homme. © Éditions de la Maison des sciences de l'homme. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Firstly, in sociolinguistics and translation studies, the article offers an empirically‐grounded account of language and translation policies in a global organisation. It contributes to a growing body of research on language ideologies and multilingualism in NGOs and INGOs in the global political economy (Codó and Garrido ; Kahn and Heller ; Muehlmann and Duchêne ; Pujolar ) and on the sociolinguistics of globalisation (Blommaert ; Blommaert, Collins and Slembrouck ; Coupland ; Heller ; Maryns ). Secondly, in international relations, development studies and political science, the article contributes to ongoing debates on the legitimacy of INGOs, the paradox between INGOs’ ethos and their often corporate management style, and INGOs’ efforts to bridge the divide between the global North and South (Demars and Dijkzeul ; Lang ; Rubenstein ; Yanacopulos ).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, in sociolinguistics and translation studies, the article offers an empirically‐grounded account of language and translation policies in a global organisation. It contributes to a growing body of research on language ideologies and multilingualism in NGOs and INGOs in the global political economy (Codó and Garrido ; Kahn and Heller ; Muehlmann and Duchêne ; Pujolar ) and on the sociolinguistics of globalisation (Blommaert ; Blommaert, Collins and Slembrouck ; Coupland ; Heller ; Maryns ). Secondly, in international relations, development studies and political science, the article contributes to ongoing debates on the legitimacy of INGOs, the paradox between INGOs’ ethos and their often corporate management style, and INGOs’ efforts to bridge the divide between the global North and South (Demars and Dijkzeul ; Lang ; Rubenstein ; Yanacopulos ).…”
Section: Introductionmentioning
confidence: 99%
“…Tour guides, people setting up tourism sites, and people managing language on tourism sites all do added-value language work by making choices about language elements that authenticate the tourist experience (Moïse et al 2006, Pujolar 2006, Jaworski & Thurlow 2010, Pujolar & Jones 2012. Working out the relations and tensions among code values is an ongoing workplace process (e.g., in nongovernmental organizations and in media production; Kahn & Heller 2006, Lamarre & Lamarre 2006 and appears in the compartmentalization of communicative tasks aboard a Canadian naval vessel (Daveluy 2012). Even deeply politicized language revival can be revalued to suit a neoliberal order, as with Taylorizing Basque-language planning for bilingual businesses (Urla 2012).…”
Section: Arimentioning
confidence: 99%
“…In recent years, issues of language and translation in the work of INGOs have started to be raised in various humanities disciplines, such as disaster management, development studies, sociolinguistics and translation studies (Codó and Garrido 2010;Footitt, Crack, and Tesseur 2020;Garrido 2017;Kahn and Heller 2006;O'Brien et al 2018;O'Brien and Federici 2019;Roth 2019;Tesseur 2018). Research has found that INGOs often do not plan for language and translation needs in their international development and humanitarian operations, and that they tend to opt for ad-hoc translation solutions in which multilingual staff or volunteers often act as translators or interpreters to ensure successful communication between NGO staff and local communities (Federici et al 2019;Footitt et al 2020).…”
mentioning
confidence: 99%